THU0599 Validation of the Dutch-Flemish Promis Pain Behavior and Pain Interference Item Banks in Patients with Rheumatoid Arthritis. (9th June 2015) - Crins, M.H.; Terwee, C.B.; Westhovens, R.; van Schaardenburg, D.; Smits, N.; Joly, J.; Verschueren, P.; Van der Elst, K.; Cella, D.; Cook, K.F.; Dekker, J.; Boers, M.; et al.
Abstract : Background: In the assessment of patients with rheumatoid arthritis (RA) it is important to measure pain behavior and pain interference. The National Institutes of Health's Patient-Reported Outcomes Measurement Information System (PROMIS) initiative developed item banks for measuring pain behavior and pain interference. These PROMIS item banks were translated into Dutch-Flemish language according to the FACIT methodology. Objectives: The aim of current study was to validate the Dutch-Flemish translation of the PROMIS Pain Behavior (DF-PROMIS-PB) and Pain Interference (DF-PROMIS-PI) item banks in Dutch and Flemish RA patients. Methods: 826 Dutch and 618 Flemish RA patients completed a paper-and-pencil or web-based survey, including the full DF-PROMIS-PB (39 items, 6-point Likert scale) and DF-PROMIS-PI (40 items, 5-point Likert scale). One-factor confirmatory factor analysis assessed unidimensionality. Item response theory (IRT) models evaluated the item characteristics of the two item banks, to facilitate future development of computer adaptive tests (CAT). A graded item response model (GRM) was fitted and construct validity was studied. Ordinal regression models evaluated Differential Item Functioning (DIF) for e.g. language (Dutch-Flemish vs. English and Dutch vs. Flemish), to analyse cross-cultural validity. Results: Current analyses support unidimensionality of the DF-PROMIS-PB and DF-PROMIS-PI (CFI=0.975;0.997 respectively and TLI=0.974;0.997 respectively). The first factor accounted for 49% (DF-PROMIS-PB) respectively 81% (DF-PROMIS-PI) of the questionnaire variance. Thirteen out of 741 (1.8%) DF-PROMIS-PB item pairs and 20 out of 780 (2.6%) DF-PROMIS-PI item pairs were marked as possibly locally dependent. The data of the two item banks fit the GRM, and showed good coverage across the pain behavior and pain interference continuum. Further analyses of the DF-PROMIS-PB and the DF-PROMIS-PI are in progress and will be presented at the conference. Conclusions: The first results indicate that the items of the DF-PROMIS-PB and the DF-PROMIS-PI fit a GRM and demonstrate good coverage across the range of the pain behavior and pain interference domain. The interim conclusion is that the DF-PROMIS-PB and DF-PROMIS-PI can be used to develop a CAT for measuring pain behavior and pain interference in Dutch and Flemish RA patients. Disclosure of Interest: None declared